MEDIA FLASHCARD DALAM PEMBELAJARAN TARI DI SEKOLAH DASAR : MEDIA FLASHCARD DALAM PEMBELAJARAN TARI DI SEKOLAH DASAR - Nabilla Nur Kasih Kusuma Putri (Jurnal Pendidikan Dasar, 2022)
Education is responsible for integrating, fostering and nurturing in developing the talents and creative abilities of students. What is the teacher's role in fostering children's creativity. This study aims to find out how Flash Card media is to foster children's creativity in learning dance art in elementary schools. The research method uses a qualitative approach. Data collection techniques using observation and interviews. The result of this research is the teacher makes changes related to the learning process in the focus of behavioristic learning theory, learning methods and Flash Card media in order to develop children's dancing creativity. By using the theory from Wallas through the stages of preparation, incubation, illumination and verification, children can turn into active and creative individuals. Flash Card media is the result of teacher innovation in changing a learning process. This media can bring out the creativity and activeness of children in expressing themselves in the form of a movement so that children can be more active and creative from seeing pictures to dance movements. It is hoped that the results of this study can be used as reference material or development for further research.